1992
DOI: 10.1016/0140-6736(92)92292-n
|View full text |Cite
|
Sign up to set email alerts
|

Controlled trial of pulse methylprednisolone versus two regimens of pulse cyclophosphamide in severe lupus nephritis

Abstract: Pulse cyclophosphamide is more effective than prednisone alone in preventing renal failure in lupus nephritis. We undertook a randomised, controlled trial to find out whether pulse methylprednisolone could equal pulse cyclophosphamide in preserving renal function in patients with lupus nephritis, and whether there was a difference between long and short courses of pulse cyclophosphamide in preventing exacerbations. 65 patients (60 female, 5 male; median [range] age 29 [10-48] years) with severe lupus nephritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
410
3
18

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 745 publications
(439 citation statements)
references
References 21 publications
8
410
3
18
Order By: Relevance
“…Previous reports (11, 13,[17][18][19][20][21] did not analyze in detail the effect of method of CYC administration on rate of relapse. In systemic vasculitis, Fauci et a1 (28) demonstrated that daily oral CYC is more effective than intravenous CYC in preventing new events of vasculitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports (11, 13,[17][18][19][20][21] did not analyze in detail the effect of method of CYC administration on rate of relapse. In systemic vasculitis, Fauci et a1 (28) demonstrated that daily oral CYC is more effective than intravenous CYC in preventing new events of vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…However, followup of patients in these studies was short or was not mentioned in the reports (11, 13,[17][18][19]. Boumpas et a1 (20) and Wagner-Weiner et a1 (21) found that short courses of intravenous CYC pulses were associated with a higher rate of disease exacerbation than were longer courses. Information regarding the influence of demographic and clinical variables, renal histology, and methods of CYC administration is lack-ing.…”
mentioning
confidence: 99%
“…Though high-dose IV CYC in combination with glucocorticoids viewed as the most effective immunosuppressive medication for LN, no final conclusion has yet been reached on this matter so far. With development of further research into this issue, several investigators have raised concerns about the high-dose CYC regimen for the treatment of SLE, especially the risks of infection and ovarian failure [9,10]. Meanwhile, other researchers put forward a question on whether the patients with mild damage should use this regimen or not.…”
Section: Discussionmentioning
confidence: 99%
“…One of the plausible reasons for choosing CYC is that data on the use of MMF for severe LN are still limited as compared to those on the use of CYC, which has a long history of clinical trials and clinical treatment for LN. For example, one of the NIH clinical trials demonstrated that long-course CYC therapy can prevent deterioration of renal function more effectively than mPSL pulse therapy in patients with severe LN [11].…”
Section: Discussionmentioning
confidence: 99%